2022
DOI: 10.1002/advs.202201133
|View full text |Cite
|
Sign up to set email alerts
|

SERS Hotspot Engineering by Aerosol Self‐Assembly of Plasmonic Ag Nanoaggregates with Tunable Interparticle Distance

Abstract: Surface‐enhanced Raman scattering (SERS) is a powerful sensing technique. However, the employment of SERS sensors in practical applications is hindered by high fabrication costs from processes with limited scalability, poor batch‐to‐batch reproducibility, substrate stability, and uniformity. Here, highly scalable and reproducible flame aerosol technology is employed to rapidly self‐assemble uniform SERS sensing films. Plasmonic Ag nanoparticles are deposited on substrates as nanoaggregates with fine control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…In plants, most peaks of the SERS spectra are attributed to adenine-containing materials, flavins, chlorophyll, and lipids [ 84 ]. SERS has been used extensively for the detection and determination of a wide range of biological molecules in plants [ 85 ], such as for plant hormones [ 86 , 87 ], and have practical applications in food-safety diagnostics such as for pesticide detection [ 88 , 89 ] ( Table 3 ).…”
Section: The Designs and Principles Of Nanosensors Used In Plant Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…In plants, most peaks of the SERS spectra are attributed to adenine-containing materials, flavins, chlorophyll, and lipids [ 84 ]. SERS has been used extensively for the detection and determination of a wide range of biological molecules in plants [ 85 ], such as for plant hormones [ 86 , 87 ], and have practical applications in food-safety diagnostics such as for pesticide detection [ 88 , 89 ] ( Table 3 ).…”
Section: The Designs and Principles Of Nanosensors Used In Plant Sciencementioning
confidence: 99%
“…SERS utilising gold nanoparticles has been used in the real-time monitoring of pesticide translocation in tomato plant tissues, including in the leaves and flowers [ 226 ]. In addition, flame aerosol technology has been used to rapidly self-assemble uniform SERS sensing films to detect pesticides [ 89 ]. This technology combines particle synthesis and facile film fabrication in a cost-effective and single process step.…”
Section: Nanosensor Applications In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials for providing hot spots and enhancing Raman signals play a crucial role in SERS technology. 34,35 At the same time, the training of CNN models requires large amounts of data and high-quality datasets; therefore, a base with good uniformity and repeatability is also essential. Based on the above two points, the properties of Ag NPs and the paper-based Ag NP substrate were characterized as shown in Fig.…”
Section: Characterization Of Agnps and Paper-based Ag Np Substratementioning
confidence: 99%
“…[36,38] It has been previously shown that tuning the dielectric SiO 2 spacer content in flame-made plasmonic nanoaggregates controls the interparticle distance of individual nanospheres which directly affects their optical extinction by plasmonic coupling. [36,[38][39][40] First, we studied the properties of Au nanocoatings as a function of SiO 2 content to fine-tune the photothermal effect in the NIR region. The UV/vis spectra in Figure 2a Second, to investigate whether the tuning of the plasmonic coupling can be attributed to varying dielectric spacer content in the Au/SiO 2 nanocoatings produced here, we analyzed the nanoscale morphology of Au/SiO 2 NPs via scanning transmission electron microscopy (STEM) images combined with energy-dispersive X-ray spectroscopy (EDX) and energy-loss spectroscopy (EELS).…”
Section: Characterization Of Plasmonic Au/sio 2 Nanoaggregatesmentioning
confidence: 99%